Edukasi Kebutuhan Status Gizi Pada Ibu Hamil Trimester Pertama di PMB M Ginting Kecamatan Siantar Martoba Kabupaten Simalungun Tahun 2023 - Parningotan Simanjuntak; Septimeliani Sihaloho; Nopalina Suyanti Damanik; Ribur Sinaga; Astaria Br Ginting (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2023)
Background: Malnutrition during pregnancy will affect the growth, formation and development of organs as well as the function of the fetus's organs becoming less than optimal, it is feared that congenital defects will occur in the baby born, it could even result in the baby's head being small due to a lack of fetal nutritional intake for brain development so that brain development is not optimal. . Apart from that, infant deaths due to LBW, namely less than 2.5 kg and premature babies, are also due to the mother's poor nutritional status (Nurul Pujiastuti, 2015). The aim of this community service program (PKM) is to increase education on nutritional needs for pregnant women in the first trimester in PMB M Ginting, Siantar Martoba District, Simalungun Regency in 2023. The methods used include 1) identification of pregnant women in PMB M Ginting, Siantar Martoba District, Simalungun Regency); 2) preparation of materials and steps for education on nutritional needs for pregnant women in the first trimester); 3) implementation of education on nutritional needs for pregnant women in the first trimester). Results Based on the results of implementing community service for outpatient pregnant women in PMB M Ginting, Siantar Martoba District, Simalungun Regency, in 2023 there are a total of 30 pregnant women as members, of which the majority are 20-35 years old, 27 pregnant women (90%), < 20 years old, 3 pregnant women (10%), all participants were enthusiastic about carrying out educational activities on the nutritional needs of pregnant women. Providing information regarding increasing the use of the registration application for Education on Nutritional Needs for Pregnant Women in the First Trimester in order to improve the comfort of pregnant women.